Management of Planning and Learning Design in the Majelis Al-Lughah Al-‘Arabiyah Programe (MLA) in Institut Agama Islam Negeri Bengkulu - Mahdatila, Tiara Shinta; Sianipar, Tiara S M; Oktalia, Beni; Arifa, Zakiyah (UIN Syekh Wasil Kediri, Indonesia, 2020)
The Arabic Language Council (MLA) is one of the pioneering programs at Bengkulu Islamic State University in improving the quality of Arabic language learning. Learning in this program is presented more enjoyably and strengthens intimacy among students, so that it can help Arabic students in solving problems while studying Arabic. In this paper, the researchers discuss the planning management and education design in the Arabic Language Council (MLA) program at the Islamic State University Bengkulu. This research aims to describe the planning management and education design in the MLA program. In this research, researchers used descriptive qualitative research in the case study design. As for the method of data collection, it means interviewing notes and documents. The researchers used the metadata analysis method. This research uses analysis from Miles and Huberman. The result of the research is the activities of this program uses planning based on the time dimension that consists of weekly, monthly and yearly programs. Mutual legal assistance program planning also uses joint planning. The aspects of the organization are clear. There are clear objectives and organizational structures to achieve the goals